Removal of Phosphate Ions from Aqueous Solution Using Anthracite - Rahman, Mohammad Arifur; Azam, Tamanna; Alam, A. M. Shafiqul (Dhaka University Journal of Science, 2012)
Anthracite was used as an adsorbent to remove excess phosphate from wastewater. Anthracite used in the present study is environmentally friendly and of cost effective. The adsorption study was carried out using different particle size of adsorbents, different concentration of phosphate solution ranging from 25.0 mg/L to 100.0 mg/L, different pH values ranging from 0.5 to 11.5 along with different adsorbent amount from 1.0 g to 5.0 g. Flow rate was also varied in the range of 0.6 mL/min to 1.8 mL/min. Adsorption column methods show the optimum removal of phosphate under the following conditions: initial phosphate concentration 25 mg/L, initial volume 25.0 mL, flow rate 1.0 mL/min adsorbent amount 2.0 g, particle size, < 90?m. This removal method may provide a solution to the removal phosphate from wastewater in Bangladesh as well as other countries of the world. DOI: http://dx.doi.org/10.3329/dujs.v60i2.11490 Dhaka Univ. J. Sci. 60(2): 181-184, 2012 (July)